Selection of Inhibitors for Carbon Dioxide (CO\(_2\)) Corrosion - Mainier, Fernando B.; Mainier, Renata Jogaib; Medeiros, Ailton Macedo; Farneze, Humberto Nogueira (Chemical and Materials Sciences: Developments and Innovations Vol. 9, 2025)
The occurrence of carbon dioxide (CO2) in many industrial processes promotes massive corrosion by crevices and pitting in the carbon steel that makes up most industrial processing equipment. This study presents the properties of carbonic acid (H2CO3) and, consequently, the mechanisms of its corrosive action. The mechanisms by which corrosion inhibitors work to inhibit the corrosive process caused by CO2 in the vapor and liquid phases are presented. Commercial formulations used to inhibit carbon dioxide corrosion must meet a number of quality assurance criteria and/or specifications, including solubility, active matter content, volatility, foaming tendency, residues and deposits. Evaluation and monitoring of the inhibiting ability of commercial formulations should be determined based on laboratory, pilot and field tests using carbon steel or other metal or alloy coupons. Finally, the toxicity of active substances and solvents used in commercial corrosion inhibitor formulations must be evaluated for potential harm to humans and the environment.